Implementasi Tugas Proyek Berkelanjutan pada Mata Pelajaran Pemesinan Bubut dan Pemesinan Frais: Studi Kasus di SMKN 7 Kota Serang - Pratama, Fajar Wahyu; Anaam, Ibnu Khoirul; Putra, Ananda Yhuto Wibisono; Alfian, Riski; Susanto, Triyo (Edu Berkah Khatulistiwa, 2025)
Vocational education in SMK aims to prepare students to become skilled labourers who are ready to enter the industrial world. Subjects such as lathe and milling machining play an important role in developing students' technical skills. This research aims to identify challenges in the implementation of Project-Based Learning (PjBL)-based sustainable project assignments in these subjects at SMKN 7 Serang City, as well as explore strategies to improve learning effectiveness. The research used a case study approach with qualitative descriptive method. Data was collected through direct observation and documentation. The results show that although the PjBL method helps students develop technical skills and soft skills, there are some obstacles. Challenges include lack of facilities, differences in students' ability to operate machines, and non-conformity with the ideal stages of PjBL, such as project design and schedule preparation which are still dominated by teachers. But in each stage of PjBL that is implemented, there are still some that are not in accordance with the application of PjBL. In addition, time management is the main obstacle in project completion. This study recommends increasing the role of students in all stages of PjBL, improving practical facilities, and strengthening supervision and guidance. In conclusion, optimal implementation of PjBL can improve technical skills and student readiness to face the world of work.